PREPARATION OF HIGH SCHOOL’S FINANCIAL MANAGEMENT TEACHING MATERIALS FOR BATAM KALLISTA SCHOOL - Lady Lady; Vitrian Anggraini (ConCEPt - Conference on Community Engagement Project, 2022)
This practical work project aims to create teaching materials for Kallista Batam High School’s level of financial management subject. The data was collected by conducting direct interviews with teachers at Kallista Batam School, document study techniques using sources from the Cambridge International AS and A Level Business Coursebook, which is a financial management material guide book for Kallista Batam High School and the official website of the Kallista Batam School. The project outputs produced and submitted to the Kallista Batam School are several modules or teaching materials in digital forms such as PowerPoint file, which consists of material made in PowerPoint slides per chapter or section, question bank that consists of a collection of questions according to the part of the material being taught, a collection of a video consisting of videos related to the material and a summary consisting of additional information and important notes on the material in pdf form.